Fuel cell electrode
By optimizing the manufacturing conditions and using a high oxygen permeation ionomer, the fuel cell electrode achieves reduced gas diffusion resistance and improved current-voltage characteristics, addressing the challenges of power generation performance across varying temperature and humidity conditions.
Patent Information
- Application Number
- JP2023145772
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-08
- Publication Date
- 2025-03-21
AI Technical Summary
Solid polymer fuel cells face challenges in achieving high power generation performance across a wide range of temperature and humidity conditions due to trade-offs in catalyst layer design, such as increased proton resistance and gas diffusion resistance.
A fuel cell electrode with a scattering length density change rate of 25% or less, a water content reduction rate of 80% or less, and/or an ionoma amount increase rate of 23% or less, achieved by optimizing the manufacturing conditions and using a high oxygen permeation ionomer.
The optimized fuel cell electrode reduces gas diffusion resistance, improves current-voltage characteristics, and decreases the amount of catalyst required, thereby enhancing power generation performance and reducing costs.
Smart Images

Figure 2025039033000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an electrode for a fuel cell, and more specifically to an electrode for a fuel cell suitable as an electrode (catalyst layer) for a polymer electrolyte fuel cell. [Background technology]
[0002] A polymer electrolyte fuel cell is equipped with a membrane electrode assembly (MEA) in which electrodes (catalyst layers) are bonded to both sides of an electrolyte membrane. The catalyst layer is the reaction field for the electrode reaction, and is generally made of a composite of carbon carrying an electrode catalyst such as platinum and a catalyst layer ionomer. A gas diffusion layer is usually further disposed on the outside of the catalyst layer. The gas diffusion layer is used to supply reactant gas and electrons to the catalyst layer, and is made of carbon paper, carbon cloth, or the like. Furthermore, a separator having a gas flow path is disposed on the outer side of the gas diffusion layer. A polymer electrolyte fuel cell generally has a structure (stack structure) in which a plurality of unit cells each having such an MEA, a gas diffusion layer, and a separator are stacked.
[0003] Polymer electrolyte fuel cells are required to show high power generation performance in a wide range of temperature and humidity environments, from low temperature and high humidity conditions to high temperature and low humidity conditions. To achieve both of these performances, it is necessary to improve the catalyst layer where the reaction occurs. To improve power generation performance under high temperature and low humidity conditions, it is necessary to lower the proton resistance and reduce IR loss. Furthermore, to improve power generation performance under low temperature and high humidity conditions, it is necessary to increase the porosity of the catalyst layer and reduce gas diffusion resistance by improving water discharge performance. However, these properties have a trade-off relationship: for example, if the volume fraction of the ionomer is increased, the proton resistance can be reduced, but the porosity decreases accordingly.
[0004] In order to solve this problem, various proposals have been made in the past. For example, Patent Document 1 states: (a) preparing a polymer electrolyte comprising a random copolymer of a perfluoromonomer having an asymmetric five-membered ring structure and a perfluoromonomer having a pendant structure composed of a perfluoro group having a sulfonic acid group; (b) preparing Pt-supported carbon by supporting Pt on a carbon support having a hydrophobic surface; (c) preparing a catalyst ink containing a polymer electrolyte and Pt-supported carbon; (d) Spraying the catalyst ink onto the surface of the substrate and drying it to form an electrode; (e) The electrodes are thermally transferred onto the cathode side of the electrolyte membrane at 150°C. The resulting membrane electrode assembly is disclosed.
[0005] The same document states: (A) In an electrode, if the hydrophilic and hydrophobic domains of the polymer electrolyte are excessively phase-separated, the continuously existing hydrophilic domains will inhibit gas permeation, resulting in a decrease in electrode performance; (B) When a polymer electrolyte having a bulky, rigid, asymmetric five-membered ring (1,3-dioxole ring) structure in the main chain is used as the catalyst layer ionomer, the degree of separation of hydrophilic domains increases compared to when a polymer electrolyte having a flexible tetrafluoroethylene chain is used as the catalyst layer ionomer, thereby increasing the cell voltage; and (C) In the case where a polymer electrolyte having a bulky, rigid, asymmetric five-membered ring (1,3-dioxole ring) structure in the main chain is used as the catalyst layer ionomer, when the surface of the carbon support is hydrophobic, the hydrophilic domains become more discrete than when the surface of the carbon support is hydrophilic, and this increases the cell voltage. is stated.
[0006] Non-Patent Document 1 states: (a) A method of spin-coating a Nafion (registered trademark) solution onto a Pt / Si substrate surface, followed by vacuum annealing at 140°C for 2 hours, and then measuring the neutron reflectivity of the resulting thin film by utilizing the contrast change between H2O and D2O; and (b) The scattering length density profile of Nafion® molecules and the volume fraction profile of water in the depth direction of a wet Nafion® film in contact with Pt obtained by this method. has been disclosed.
[0007] The same document states: (A) A segregation layer is formed on the Pt surface, in which the concentration of Nafion® molecules is increased and the concentration of water molecules is decreased; and (B) The thickness of the segregation layer is about 3 nm, which roughly corresponds to the diameter of the rod-like micelles formed by the aggregation of Nafion® molecules in the solution. is stated.
[0008] Reducing the cost of fuel cells is an issue for the widespread use of fuel cell vehicles. Costs can be reduced by reducing the amount of catalyst used in the electrodes, but in order to maintain current-voltage characteristics with a reduced amount of catalyst, it is necessary to reduce the gas diffusion resistance of the electrodes. In particular, since the output density of a fuel cell depends on the oxygen reduction ability of the cathode, it is important to reduce the gas diffusion resistance of the cathode. However, when perfluorocarbon sulfonic acid polymers such as Nafion® are used as the catalyst layer ionomer for the cathode, there is a limit to the achievable current-voltage characteristics. This is thought to be because a segregation layer with a high concentration of Nafion® molecules is formed on the Pt surface, which may increase the gas diffusion resistance (see Non-Patent Document 1).
[0009] To solve this problem, it is possible to use an ionomer having an asymmetric five-membered ring (1,3-dioxole ring) as the cathode catalyst layer ionomer, as described in Patent Document 1. Such an ionomer has a lower oxygen gas diffusion resistance than Nafion (registered trademark), and is therefore also called a "high oxygen permeable ionomer." However, there is a limit to the achievable current-voltage characteristics when a highly oxygen-permeable ionomer is simply used as the cathode catalyst layer ionomer. [Prior art documents] [Patent documents]
[0010] [Patent Document 1] Patent No. 6096749 [Non-patent literature]
[0011] [Non-Patent Document 1] Harada, M.; Kudo, K.; Yamada, NL, Compositional Segregation in a Cross Section of Wet Nafion Thin Film on a Platinum Surface, Chem. Lett. 2019, 48(1), 51-54 Summary of the Invention [Problem to be solved by the invention]
[0012] An object of the present invention is to provide a novel fuel cell electrode having low gas diffusion resistance. [Means for solving the problem]
[0013] In order to solve the above problems, a fuel cell electrode according to a first embodiment of the present invention comprises: an electrode catalyst including catalyst particles; an ionomer layer covering all or a part of the surface of the catalyst particle; Equipped with The scattering length density change rate (ΔSLD) represented by the formula (1) described later is 25% or less.
[0014] The fuel cell electrode according to the second embodiment of the present invention comprises: an electrode catalyst including catalyst particles; an ionomer layer covering all or a part of the surface of the catalyst particle; Equipped with The moisture content reduction rate (Δλ) represented by the formula (2) described below is 80% or less.
[0015] A fuel cell electrode according to a third embodiment of the present invention comprises: an electrode catalyst including catalyst particles; an ionomer layer covering all or a part of the surface of the catalyst particle; Equipped with The rate of increase (ΔC) in the amount of ionomer represented by the formula (3) described below is 23% or less. Effect of the Invention
[0016] The gas diffusion resistance of a fuel cell electrode correlates with the degree of ionomer segregation in the region of the ionomer layer located near the interface between the catalyst particle and the ionomer layer (hereinafter, also referred to as the "interface region"). The degree of ionomer segregation in the interface region is (a) Scattering length density change rate (ΔSLD), (b) Moisture content reduction rate (Δλ), and / or (c) Ionomer amount increase rate (ΔC) It can be expressed as: Specifically, a small rate of change in scattering length density, a small rate of decrease in water content, and a small rate of increase in the amount of ionomer each indicate that segregation of the ionomer is suppressed in the interface region.
[0017] The degree of segregation of the ionomer in the interfacial region depends primarily on the type of ionomer and the heat treatment conditions during electrode or fuel cell fabrication. Therefore, by optimizing the manufacturing conditions, a fuel cell electrode can be obtained in which the scattering length density change rate is 25% or less, the water content reduction rate is 80% or less, and / or the ionomer amount increase rate is 23% or less. [Brief description of the drawings]
[0018] [Figure 1] FIG. 2 is a schematic diagram of a fuel cell electrode (catalyst layer). [Diagram 2] 1 shows a structure in the vicinity of the interface between the ionomer and platinum, evaluated by neutron reflectometry for the ionomer thin film on the platinum thin film obtained in Example 1. [Diagram 3] 1 shows a structure in the vicinity of the interface between the ionomer and platinum, evaluated by neutron reflectometry for the ionomer thin film on the platinum thin film obtained in Comparative Example 1. [Figure 4] 3 shows the current-voltage characteristics of the fuel cell obtained in Example 2. [Diagram 5] 4 shows the current-voltage characteristics of the fuel cell obtained in Comparative Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] [Configuration 1] an electrode catalyst including catalyst particles; an ionomer layer covering all or a part of the surface of the catalyst particle; Equipped with The scattering length density change rate (ΔSLD) expressed by the following formula (1) is 25% or less. Electrodes for fuel cells.
[0020] ΔSLD=(SLD2-SLD1)×100 / SLD1…(1) however, SLD1 is the average scattering length density of the bulk region of the ionomer layer; SLD2 is the maximum value of the scattering length density in the interfacial region of the ionomer layer; The "interface region" refers to a region within the ionomer layer that is from the interface between the catalyst particle and the ionomer to a thickness of 10 nm. The "bulk region" refers to the region within the ionomer layer excluding the interface region; The "scattering length density" is the scattering length of a neutron per unit volume at an arbitrary position in the ionomer layer, measured and calculated using a neutron reflectance method under conditions of a relative humidity of 50% or more.
[0021] [Configuration 2] an electrode catalyst including catalyst particles; an ionomer layer covering all or a part of the surface of the catalyst particle; Equipped with The moisture content reduction rate (Δλ) expressed by the following formula (2) is 80% or less. Electrodes for fuel cells.
[0022] Δλ=(λ1-λ2)×100 / λ1…(2) however, λ1 is the average water content of the bulk region of the ionomer layer; λ2 is the minimum water content of the interfacial region of the ionomer layer; The "interface region" refers to a region within the ionomer layer that is from the interface between the catalyst particle and the ionomer to a thickness of 10 nm. The "bulk region" refers to the region within the ionomer layer excluding the interface region; The "water content" is the mass ratio of water per unit volume at any position in the ionomer layer, measured and calculated using a neutron reflectometry under conditions of a relative humidity of 50% or more.
[0023] [Configuration 3] an electrode catalyst including catalyst particles; an ionomer layer covering all or a part of the surface of the catalyst particle; Equipped with The increase in the amount of ionomer (ΔC) represented by the following formula (3) is 23% or less. Electrodes for fuel cells.
[0024] ΔC = (C2 - C1) × 100 / C1 … (3) however, C1 is the average amount of ionomer in the bulk region of the ionomer layer; C2 is the maximum amount of ionomer in the interfacial region of the ionomer layer; The "interface region" refers to a region within the ionomer layer that is from the interface between the catalyst particle and the ionomer to a thickness of 10 nm. The "bulk region" refers to the region within the ionomer layer excluding the interface region; The "ionomer amount" is the proportion of the mass of the ionomer per unit volume at an arbitrary position of the ionomer layer, measured and calculated using a neutron reflectance method under conditions of a relative humidity of 50% or more.
[0025] [Configuration 4] 4. The fuel cell electrode according to any one of configurations 1 to 3, wherein the electrode catalyst further includes a carrier that supports the catalyst particles.
[0026] [Configuration 5] 5. The fuel cell electrode according to any one of configurations 1 to 4, wherein the ionomer layer contains a highly oxygen-permeable ionomer.
[0027] [Configuration 6] 6. The fuel cell electrode according to any one of configurations 1 to 5, wherein the ionomer layer contains a highly oxygen-permeable ionomer having a molecular structure represented by the following formula (4): -[C3O2F2(Rf1)(Rf2)] x -[CF2-CF(ORf3-SO3H)] y - …(4) however, Rf1 and Rf2 are each F or a perfluoroalkyl group having 1 to 10 carbon atoms, and the perfluoroalkyl group may have an oxygen atom in the molecular chain. Rf3 is -(CF2CF(CF3)O) h -(CF) i where h is an integer from 0 to 3 and i is an integer from 1 to 10; x and y are each 1 or greater, x / y is between 0.63 and 4.2. The weight average molecular weight is 5,000 or more and 300,000 or less.
[0028] An embodiment of the present invention will be described in detail below. [1. Electrodes for fuel cells] The fuel cell electrode according to the present invention comprises: an electrode catalyst including catalyst particles; an ionomer layer covering all or a part of the surface of the catalyst particle; It is equipped with: The electrode catalyst may further include a carrier for supporting the catalyst particles.
[0029] [1.1. Electrocatalyst] [1.1.1. Catalyst particles] [A. Materials] In the present invention, the material of the catalyst particles is not particularly limited as long as it has activity in the hydrogen oxidation reaction or the oxygen reduction reaction. Examples of materials for the catalyst particles include: (a) Precious metals (Pt, Au, Ag, Pd, Rh, Ir, Ru, Os), (b) An alloy containing two or more precious metal elements; (c) Alloys containing one or more precious metal elements and one or more base metal elements (e.g., Fe, Co, Ni, Cr, V, Ti, etc.); etc.
[0030] Among these, the catalyst particles are preferably made of Pt or a Pt alloy, since they have high activity in the electrode reaction of the fuel cell. Examples of Pt alloys include Pt-Fe alloys, Pt-Co alloys, Pt-Ni alloys, Pt-Pd alloys, Pt-Cr alloys, Pt-V alloys, Pt-Ti alloys, Pt-Ru alloys, and Pt-Ir alloys.
[0031] [B. Average particle size] "Average particle size of catalyst particles" refers to the average maximum dimension of catalyst particles measured under a microscope for 20 or more randomly selected catalyst particles. The average particle size of the catalyst particles is not particularly limited, and the most suitable average particle size can be selected according to the purpose. In general, if the average particle size of the catalyst particles is too small, the catalyst particles tend to dissolve. Therefore, the average particle size is preferably 1 nm or more. On the other hand, if the average particle size of the catalyst particles is too large, the mass activity decreases. Therefore, the average particle size of the catalyst particles is preferably 20 nm or less. The average particle size is preferably 10 nm or less, and more preferably 5 nm or less.
[0032] [C. Loading amount] The term "supported amount of catalyst particles" refers to the ratio of the mass of the catalyst particles to the total mass of the electrode catalyst when the catalyst particles are supported on a carrier. The amount of catalyst particles supported is not particularly limited, and an optimal amount can be selected depending on the purpose. In general, if the amount of catalyst particles supported is too small, the thickness of the catalyst layer required to obtain a predetermined weight becomes large, and the electronic resistance, proton resistance, and / or gas diffusion resistance of the catalyst layer increases. Therefore, the amount of catalyst particles supported is preferably 5 mass% or more. The amount is more preferably 10 mass% or more, and more preferably 15 mass% or more. On the other hand, if the amount of catalyst particles supported is excessive, the catalyst particles may aggregate on the surface of the carrier (conductive particles), which may result in a decrease in the activity of the electrode catalyst. Therefore, the amount of catalyst particles supported is preferably 60 mass% or less. The amount is more preferably 50 mass% or less, and even more preferably 40 mass% or less.
[0033] 1.1.2. Carrier [A. Materials] The electrode catalyst may consist of catalyst particles alone, or may include a carrier that supports the catalyst particles. When the electrode catalyst includes a carrier, fine catalyst particles can be supported on the surface of the carrier in a highly dispersed manner, improving the catalyst utilization rate. In the present invention, the material of the support is not particularly limited as long as it is a material that has electrical conductivity and can be used in a fuel cell environment.
[0034] Examples of the carrier include: (a) carbon black, (b) Porous carbon such as mesoporous carbon; (c) SnO2, nonstoichiometric titanium dioxide (TiO x Conductive oxide particles made of conductive metal oxides or composite metal oxides such as etc. The carrier may be any one of these, or a combination of two or more of them.
[0035] [B. Average particle size] The "average particle size of the carrier" is the volume-based median diameter (D 50 ) The average particle size of the carrier is not particularly limited, and the most suitable particle size can be selected according to the purpose. In general, if the average particle size of the carrier is too small, the bonds between the carriers become poor, and the electronic resistance may become large. Therefore, the average particle size is preferably 0.1 μm or more. The average particle size is more preferably 0.3 μm or more, and more preferably 0.5 μm or more. On the other hand, if the average particle size of the carrier becomes too large, the uniformity of the catalyst layer is lost, and in some cases, the electrolyte membrane may be damaged when pressed. Therefore, the average particle size is preferably 20 μm or less. The average particle size is more preferably 10 μm or less, and even more preferably 5 μm or less.
[0036] [1.2. Ionomer layer] The entire or part of the surface of the catalyst particle is covered with an ionomer layer. The ionomer needs to be in a moderate water content state in order to exhibit proton conductivity. Therefore, in the operating environment of the fuel cell, the ionomer layer usually consists of a mixed layer of the ionomer, water, and fine voids of nanometer size.
[0037] [1.2.1. Ionomer materials] In the present invention, the material of the ionomer is not particularly limited. Examples of ionomer materials include: (a) perfluorocarbon sulfonic acid polymers such as Nafion®, Flemion®, Aciplex®, and Aquivion®; (b) Highly oxygen permeable ionomer etc. The ionomer layer may contain any one of these ionomers, or may contain two or more of them.
[0038] Here, the term "highly oxygen-permeable ionomer" refers to a polymer compound that contains an acid group and a cyclic structure in its molecular structure. The highly oxygen-permeable ionomer has a high oxygen permeability coefficient because it contains a cyclic structure in its molecular structure. Therefore, when this ionomer is used as a cathode ionomer, the oxygen transfer resistance at the interface with the catalyst particles becomes relatively small. In other words, the "highly oxygen-permeable ionomer" refers to an ionomer having an oxygen permeability coefficient higher than that of perfluorocarbon sulfonic acid polymers such as Nafion (registered trademark).
[0039] In general, the power generation performance of a fuel cell in the high current density region is rate-limiting due to the diffusion of oxygen to the catalyst particle surface. In contrast, coating the surface of the catalyst particle with a highly oxygen-permeable ionomer improves the oxygen permeability of the catalyst layer, thereby improving the performance of the fuel cell. The molecular structure of the highly oxygen-permeable ionomer is not particularly limited as long as it exhibits a relatively small oxygen transfer resistance. In particular, ionomers containing a cyclic structure (aliphatic cyclic structure) in their molecular structure have a smaller oxygen transfer resistance than ionomers that do not contain a cyclic structure, and are therefore suitable as ionomers for coating electrode catalysts.
[0040] Examples of highly oxygen-permeable ionomers include: (a) an electrolyte polymer including a perfluorocarbon unit having an aliphatic ring structure and an acid group unit having a perfluorosulfonic acid in a side chain; (b) an electrolyte polymer including a perfluorocarbon unit having an aliphatic ring structure and an acid group unit having a perfluoroimide in a side chain; (c) an electrolyte polymer containing a unit in which perfluorosulfonic acid is directly bonded to a perfluorocarbon having an aliphatic ring structure; etc. (See References 1 to 4). [Reference 1] JP 2003-036856 A [Reference 2] International Publication No. 2012 / 088166 [Reference 3] JP 2013-216811 A [Reference 4] JP 2006-152249 A
[0041] The ionomer is preferably a highly oxygen-permeable ionomer having a molecular structure represented by the following formula (4). -[C3O2F2(Rf1)(Rf2)] x -[CF2-CF(ORf3-SO3H)] y - …(4) however, Rf1 and Rf2 are each F or a perfluoroalkyl group having 1 to 10 carbon atoms, and the perfluoroalkyl group may have an oxygen atom in the molecular chain. Rf3 is -(CF2CF(CF3)O) h -(CF) i where h is an integer from 0 to 3 and i is an integer from 1 to 10; x and y are each 1 or greater, x / y is between 0.63 and 4.2. The weight average molecular weight is 5,000 or more and 300,000 or less.
[0042] The highly oxygen-permeable ionomer represented by formula (4) is a copolymer of perfluorodimethyldioxazole and perfluoro(3-oxapent-4-ene)sulfonyl fluoride, and has a high oxygen permeability coefficient. In addition, the highly oxygen-permeable ionomer represented by formula (4) is less likely to segregate on the catalyst particle surface than perfluorocarbon sulfonic acid polymers. Therefore, the highly oxygen-permeable ionomer represented by formula (4) is particularly suitable as an ionomer constituting an ionomer layer.
[0043] [1.2.2. Ionomer content] The content of the ionomer contained in the fuel cell electrode is not particularly limited, and an optimal content can be selected depending on the purpose.
[0044] When the electrode catalyst contains a carrier, the ratio (I / C) of the mass (I) of the ionomer to the mass (C) of the carrier affects the performance of the fuel cell. In order to obtain high power generation performance in a wide range of temperature and humidity conditions, from low temperature and high humidity conditions to high temperature and low humidity conditions, it is preferable that the I / C meets certain conditions.
[0045] The ionomer is responsible for localized proton conduction around the catalyst particles. Therefore, the smaller the I / C, the better as long as a minimum level of proton conductivity can be ensured. However, if the I / C is too small, it may be difficult to transport protons to the catalyst particle surface. Therefore, the I / C is preferably 0.1 or more. The I / C is more preferably 0.2 or more, and even more preferably 0.4 or more. On the other hand, if I / C is too large, the porosity around the electrode catalyst becomes too small, and the gas diffusion resistance may increase. Therefore, I / C is preferably 1.2 or less. I / C is more preferably 1.0 or less, and even more preferably 0.8 or less.
[0046] [1.2.3. Segregation layer] [A. Definition] The "segregation layer" is defined as the following under conditions of relative humidity of 50% or more: (a) A region in which the ionomer concentration is higher than the average ionomer concentration of the ionomer layer (the ionomer concentration in the bulk region without the influence of the interface), or (b) Regions where the water concentration is low compared to the average water concentration in the ionomer layer (the water concentration in the bulk region without the influence of the interface). This refers to.
[0047] When a catalyst ink containing an electrode catalyst and an ionomer is applied to the surface of a substrate and dried, an electrode is obtained in which a composite in which the surface of the electrode catalyst is covered with an ionomer layer is aggregated. In this case, if the manufacturing conditions are inappropriate, the ionomer may be excessively adsorbed onto the surface of the catalyst particle, forming a segregation layer near the interface between the catalyst particle and the ionomer. In order to promote the electrode reaction, the reactant gas needs to diffuse through the ionomer layer and be supplied to the catalyst particle surface. However, the segregation layer increases the gas diffusion resistance of the ionomer layer, which causes a deterioration of the current-voltage characteristics. That is, in order to obtain high current-voltage characteristics, it is preferable that the ionomer layer does not include a segregation layer in the vicinity of the interface between the catalyst particle and the ionomer.
[0048] As described above, in an actual electrode, the surface of a catalyst particle is covered with an ionomer layer, and the ionomer layer is a mixed layer of an ionomer, water, and nanometer-sized fine voids. When a flat plate sample simulating the structure of such an actual electrode is prepared and exposed to a high humidity environment (50% RH or higher, preferably 70% RH or higher), all or part of the fine voids in the ionomer layer are filled with water (HO or DO). By performing neutron reflectivity measurement under such conditions, the presence or absence of a segregation layer in the interface region of an actual electrode can be indirectly known.
[0049] When neutron reflectivity measurements are performed under high humidity conditions using a flat sample, if an excessive amount of ionomer is adsorbed on the surface of the catalyst particle, the ionomer concentration in the interface region will be higher than the ionomer concentration in the bulk region, or the water concentration in the interface region will be lower than the water concentration in the bulk region. That is, (a) The formation of a segregation layer, (b) higher ionomer concentration in the interfacial region under high humidity conditions; and (c) The concentration of water in the interfacial region is reduced under high humidity conditions. are not necessarily identical, but there is a close relationship between them.
[0050] The degree of the segregation layer in the interface region is specifically as follows: (a) Scattering length density change rate, (b) the percent water content reduction; and / or (c) Ionomer amount increase rate It can be evaluated as follows. The fuel cell electrode according to the present invention may satisfy any one of these conditions, or may satisfy two or more conditions simultaneously.
[0051] [B. Scattering length density change rate] The "scattering length density change rate (ΔSLD)" refers to the value expressed by the following formula (1). ΔSLD=(SLD2-SLD1)×100 / SLD1…(1) however, SLD1 is the average scattering length density of the bulk region of the ionomer layer; SLD2 is the maximum value of the scattering length density in the interfacial region of the ionomer layer; The "interface region" refers to a region within the ionomer layer that is from the interface between the catalyst particle and the ionomer to a thickness of 10 nm. The "bulk region" refers to the region within the ionomer layer excluding the interface region; The "scattering length density" is the scattering length of a neutron per unit volume at an arbitrary position in the ionomer layer, measured and calculated using a neutron reflectance method under conditions of a relative humidity of 50% or more.
[0052] When the composition of the catalyst particles and ionomer used in the fuel cell electrode is known, a plate-shaped sample for neutron reflectivity measurement can be prepared. By using this plate-shaped sample to perform neutron reflectivity measurement utilizing the contrast change between H2O and D2O, the scattering length density in the depth direction in the ionomer layer can be obtained. The scattering length density is a physical property that is proportional to the density of the ionomer. A relatively large scattering length density indicates that the density of the ionomer is relatively high, i.e., the ionomer is segregated.
[0053] Neutron reflectivity measurement can be used to obtain a depth profile of the scattering length density. From the obtained depth profile, the average value of the scattering length density in the bulk region (SLD1) and the maximum value of the scattering length density in the interface region (SLD2) can be obtained. Furthermore, by substituting the obtained SLD1 and SLD2 into equation (1), ΔSLD can be calculated.
[0054] The degree of ionomer segregation in the interface region depends primarily on the type of ionomer and the heat treatment conditions during electrode or fuel cell manufacturing. Optimizing the manufacturing conditions can produce fuel cell electrodes with a scattering length density change rate of 25% or less. Further optimization of the manufacturing conditions can result in a scattering length density change rate of 15% or less, 10% or less, or 5% or less.
[0055] [C. Moisture content reduction rate] The "water content reduction rate (Δλ)" refers to the value represented by the following formula (2). Δλ=(λ1-λ2)×100 / λ1…(2) however, λ1 is the average water content of the bulk region of the ionomer layer; λ2 is the minimum water content of the interfacial region of the ionomer layer; The "interface region" refers to a region within the ionomer layer that is from the interface between the catalyst particle and the ionomer to a thickness of 10 nm. The "bulk region" refers to the region within the ionomer layer excluding the interface region; The "water content" is the mass ratio of water per unit volume at any position in the ionomer layer, measured and calculated using a neutron reflectometry under conditions of a relative humidity of 50% or more.
[0056] As described above, the scattering length density in the depth direction in the ionomer layer can be obtained by using neutron reflectivity measurement utilizing the contrast change between H2O and D2O. In addition, if the depth direction profile of the scattering length density is known, the depth direction profile of the water volume fraction can be calculated (see Non-Patent Document 1). Furthermore, the water content reduction rate can be calculated based on the obtained depth direction profile of the water volume fraction.
[0057] Conversely, in regions where the ionomer concentration is high, the water concentration is low. The degree of reduction in water content in the interface region depends mainly on the type of ionomer and the heat treatment conditions during electrode or fuel cell manufacturing. By optimizing the manufacturing conditions, a fuel cell electrode with a water content reduction rate of 80% or less can be obtained. By further optimizing the manufacturing conditions, the water content reduction rate can be reduced to 20% or less, or even 5% or less.
[0058] [D. Ionomer amount increase rate] The "increase in ionomer amount" refers to a value represented by the following formula (3). ΔC = (C2 - C1) × 100 / C1 … (3) however, C1 is the average amount of ionomer in the bulk region of the ionomer layer; C2 is the maximum amount of ionomer in the interfacial region of the ionomer layer; The "interface region" refers to a region within the ionomer layer that is from the interface between the catalyst particle and the ionomer to a thickness of 10 nm. The "bulk region" refers to the region within the ionomer layer excluding the interface region; The "ionomer amount" is the proportion of the mass of the ionomer per unit volume at an arbitrary position of the ionomer layer, measured and calculated using a neutron reflectance method under conditions of a relative humidity of 50% or more.
[0059] As described above, the scattering length density in the depth direction in the ionomer layer can be obtained by using neutron reflectivity measurement that utilizes the contrast change between H2O and D2O. In addition, if the depth direction profile of the scattering length density is known, the depth direction profile of the ionomer volume fraction can be calculated. Furthermore, the ionomer amount increase rate can be calculated based on the obtained depth direction profile of the ionomer volume fraction.
[0060] The degree of ionomer segregation in the interface region depends mainly on the type of ionomer and the heat treatment conditions during electrode or fuel cell manufacturing. Optimizing the manufacturing conditions can result in a fuel cell electrode with an ionomer content increase rate of 23% or less. Further optimization of the manufacturing conditions can result in an ionomer content increase rate of 10% or less, or even 5% or less.
[0061] [1.3. Usage] The fuel cell electrode according to the present invention can be used as either a cathode or an anode. The fuel cell electrode according to the present invention has a smaller gas diffusion resistance than conventional electrodes, and is therefore particularly suitable as a fuel cell cathode.
[0062] [2. Manufacturing method of fuel cell electrodes] The method for producing an electrode for a fuel cell according to the present invention comprises the steps of: (a) preparing a catalyst ink containing an electrode catalyst and an ionomer; (b) Coat the surface of the substrate with catalyst ink and allow the coating to dry. It can be produced by the above method.
[0063] A fuel cell including the fuel cell electrode according to the present invention can be produced by transferring the fuel cell electrode produced as described above onto an electrolyte membrane. In this case, by optimizing the type of ionomer, heat treatment conditions, etc., it is possible to suppress segregation of the ionomer near the interface between the catalyst particles and the ionomer. In general, the lower the heating temperature of the electrode during electrode production, the less likely the ionomer is to segregate in the interface region.
[0064] [3. Effect] FIG. 1 shows a schematic diagram of a fuel cell electrode (catalyst layer). In FIG. 1, a fuel cell electrode is formed on the surface of an electrolyte membrane. The electrode includes an electrode catalyst in which catalyst particles (Pt) are supported on the surface of a carrier (carbon), and an ionomer layer that covers all or part of the surface of the catalyst particles. In the electrode, a complex in which the surface of the electrode catalyst is covered with an ionomer layer is aggregated, and coarse voids of micrometer size are formed between the complexes. The reaction gas supplied to the electrode is transported to the surface of the ionomer layer through the coarse voids, and further diffuses within the ionomer layer to reach the surface of the catalyst particles.
[0065] In conventional electrodes, a segregation layer with a high ionomer concentration is likely to form near the interface between the catalyst particle and the ionomer layer. The formation of the segregation layer is believed to be due to the interaction between the catalyst particle and the ionomer, which orients the ionomer molecules relative to the catalyst particle surface. In the segregation layer, the ratio of water and / or ionomer to minute nanometer-sized voids is increased, so the free volume required for gas diffusion is small. As a result, the segregation layer increases the gas diffusion resistance and causes a deterioration in the current-voltage characteristics.
[0066] In contrast, the fuel cell electrode of the present invention is substantially free of a segregation layer, and therefore the increase in gas diffusion resistance is suppressed. As a result, the current-voltage characteristics are improved compared to conventional electrodes. Furthermore, the improved current-voltage characteristics reduce the amount of catalyst required to obtain the same power generation performance, thereby reducing the cost of the fuel cell.
[0067] The gas diffusion resistance of a fuel cell electrode is correlated with the degree of ionomer segregation in the interface region. (a) Scattering length density change rate (ΔSLD), (b) Moisture content reduction rate (Δλ), and / or (c) Ionomer amount increase rate (ΔC) It can be expressed as: Specifically, a small rate of change in scattering length density, a small rate of decrease in water content, and a small rate of increase in the amount of ionomer each indicate that segregation of the ionomer is suppressed in the interface region.
[0068] The degree of segregation of the ionomer in the interfacial region depends primarily on the type of ionomer and the heat treatment conditions during electrode or fuel cell fabrication. Therefore, by optimizing the manufacturing conditions, a fuel cell electrode can be obtained in which the scattering length density change rate is 25% or less, the water content reduction rate is 80% or less, and / or the ionomer amount increase rate is 23% or less. EXAMPLES
[0069] (Example 1, Comparative Example 1) [1. Sample preparation] Ionoma has: (a) a highly oxygen-permeable ionomer represented by formula (4) (Example 1), or (b) Nafion (registered trademark) (Comparative Example 1) was used. The ionomer was dissolved in 1-propanol to obtain an ionomer solution having an ionomer concentration of 1 mass%.
[0070] A platinum thin film was formed on a silicon substrate using a sputtering method. Then, an ionomer solution was spin-coated onto the surface of the platinum thin film (2000 rpm x 30 s). The ionomer thin film was then annealed in vacuum at 120°C for 1 hour.
[0071] 2. Test Method Neutron reflectivity was measured for an ionomer thin film on a platinum thin film at the Japan Proton Accelerator Research Complex (J-PARC). Humidity was kept at about 80% RH using a saturated salt solution of KCl. The neutron reflectivity of each sample was modeled with a multi-layer structure. Each layer had a different scattering length density. The difference in scattering length density within the ionomer layer reflects the ionomer concentration. The catalyst particle / ionomer layer interface can be defined as the position where the scattering length density changes abruptly.
[0072] Since the neutron reflectivity changes according to the depth profile near the interface, it is possible to analyze the contact state between the ionomer containing water and platinum. In addition, since the contact state between platinum and the ionomer affects the gas diffusion resistance of the electrode, the contact state is an index of the electrode performance.
[0073] [3. Results] Figure 2 shows the structure near the interface between the ionomer and platinum, evaluated by neutron reflectometry for the ionomer thin film on the platinum thin film obtained in Example 1. In the case of Example 1, it was confirmed that a water-containing ionomer thin film with a thickness of about 300 Å (30 nm) was present on the platinum. In the case of Example 1, there was almost no change in the scattering length density throughout the ionomer thin film, and the rate of change in scattering length density was 2% or less. In addition, in the case of Example 1, the rate of decrease in water content was 5% or less, and the rate of increase in ionomer amount was 5% or less.
[0074] Figure 3 shows the structure near the interface between the ionomer and platinum, evaluated by neutron reflectometry, for the ionomer thin film on the platinum thin film obtained in Comparative Example 1. Similarly, in Comparative Example 1, it was confirmed that a thin ionomer film containing water was present on the platinum with a thickness of about 300 Å (30 nm). However, in the case of Comparative Example 1, it was found that a layer (segregation layer) with a different scattering length density was formed near the platinum surface. The thickness of the segregation layer was 38 to 53 Å (3.8 to 5.3 nm). In addition, the difference between the average scattering length density in the bulk region and the maximum scattering length density in the interface region was 0.85 × 10 -6 Å -2 This was converted into a scattering length density change rate of 26%. In addition, in the case of Comparative Example 1, the water content reduction rate was 81%, and the ionomer amount increase rate was 24%.
[0075] (Example 2, Comparative Example 2) [1. Sample preparation] Ionoma has: (a) a highly oxygen-permeable ionomer represented by formula (4) (Example 2), or (b) Nafion (registered trademark) (Comparative Example 2) was used.
[0076] A catalyst ink containing the above ionomer and Pt-supported carbon (TEC10V30E) was applied to the surface of the substrate, and the coating was dried to prepare a cathode. The Pt coverage was 0.12 mg / cm 2 The drying temperature for the coating was 80°C. Separately, an anode was prepared. Nafion (registered trademark) was used as the ionomer of the anode, and Pt-supported carbon (TEC10V30E) was used as the electrode catalyst. The Pt coverage was 0.12 mg / cm. 2 It was decided. The electrolyte membrane used was a Nafion (registered trademark) membrane (NR211).
[0077] A cathode and an anode were transferred onto both sides of the electrolyte membrane to obtain an MEA. The hot press temperature was 140° C. Furthermore, a gas diffusion layer (SIGRACET (registered trademark) 22BB) and a separator with gas channels were sandwiched on both sides of the MEA to form a fuel cell.
[0078] 2. Test Method After conditioning, the current-voltage characteristics of the fuel cell were evaluated at a cell temperature of 80°C, humidity of 80% RH, and a sweep rate of 10 mV / s.
[0079] [3. Results] FIG. 4 shows the current-voltage characteristics of the fuel cell obtained in Example 2. In the case of Example 2, the high current region (4 A / cm) where the gas diffusion resistance is large 2 ) a potential of 0.46 V was obtained. FIG. 5 shows the current-voltage characteristics of the fuel cell obtained in Comparative Example 2. In the case of Comparative Example 2, 4 A / cm 2 A potential of 0.33 V was obtained. 4 and 5 show that the fuel cell equipped with electrodes without a segregation layer has improved current-voltage characteristics compared to the fuel cell equipped with electrodes with a segregation layer.
[0080] Although the embodiment of the present invention has been described in detail above, the present invention is not limited to the above embodiment, and various modifications are possible without departing from the gist of the present invention. [Industrial Applicability]
[0081] The fuel cell electrode according to the present invention can be used in the catalyst layer on the cathode or anode side of a polymer electrolyte fuel cell or a water electrolysis device.
Claims
1. an electrode catalyst including catalyst particles; an ionomer layer covering all or a part of the surface of the catalyst particle; Equipped with The scattering length density change rate (ΔSLD) represented by the following formula (1) is 25% or less. Electrodes for fuel cells. ΔSLD=(SLD 2 -SLD 1 )×100 / SLD 1 …(1) however, SLD 1 is the average scattering length density of the bulk region of the ionomer layer, SLD 2 is the maximum value of the scattering length density in the interface region of the ionomer layer, The "interface region" refers to a region within the ionomer layer that is from the interface between the catalyst particle and the ionomer to a thickness of 10 nm. The "bulk region" refers to the region within the ionomer layer excluding the interface region; The "scattering length density" is the scattering length of a neutron per unit volume at an arbitrary position of the ionomer layer, measured and calculated using a neutron reflectance method under conditions of a relative humidity of 50% or more.
2. an electrode catalyst including catalyst particles; an ionomer layer covering all or a part of the surface of the catalyst particle; Equipped with The water content reduction rate (Δλ) represented by the following formula (2) is 80% or less. Electrodes for fuel cells. Δλ=(λ 1 -l 2 )×100 / l 1 …(2) however, λ 1 is the average water content of the bulk region of the ionomer layer, λ 2 is the minimum water content of the interfacial region of the ionomer layer, The "interface region" refers to a region within the ionomer layer that is from the interface between the catalyst particle and the ionomer to a thickness of 10 nm. The "bulk region" refers to the region within the ionomer layer excluding the interface region; The "water content" is the proportion of the mass of water per unit volume at an arbitrary position of the ionomer layer, measured and calculated using a neutron reflectometry under conditions of a relative humidity of 50% or more.
3. an electrode catalyst including catalyst particles; an ionomer layer covering all or a part of the surface of the catalyst particle; Equipped with The increase in the amount of ionomer (ΔC) represented by the following formula (3) is 23% or less. Electrodes for fuel cells. ΔC=(C 2 -C 1 )×100 / C 1 …(3) however, C 1 is the average amount of ionomer in the bulk region of the ionomer layer, C 2 is the maximum amount of ionomer in the interfacial region of the ionomer layer, The "interface region" refers to a region within the ionomer layer that is from the interface between the catalyst particle and the ionomer to a thickness of 10 nm. The "bulk region" refers to the region within the ionomer layer excluding the interface region; The "amount of ionomer" is the proportion of the mass of the ionomer per unit volume at an arbitrary position of the ionomer layer, measured and calculated using a neutron reflectometry under conditions of a relative humidity of 50% or more.
4. 4. The fuel cell electrode according to claim 1, wherein the electrode catalyst further comprises a carrier for supporting the catalyst particles.
5. 4. The fuel cell electrode according to claim 1, wherein the ionomer layer comprises a highly oxygen permeable ionomer.
6. 4. The fuel cell electrode according to claim 1, wherein the ionomer layer contains a highly oxygen-permeable ionomer having a molecular structure represented by the following formula (4): -[C 3 O 2 F 2 (Rf1)(Rf2)] x -[CF 2 -CF(ORf3-SO 3 H)] y - …(4) however, Rf1 and Rf2 each represent F or a perfluoroalkyl group having 1 to 10 carbon atoms, and the perfluoroalkyl group may have an oxygen atom in the molecular chain; Rf3 is -(CF 2 CF(CF 3 )O) h -(CF) i -, h is an integer from 0 to 3, i is an integer from 1 to 10, x and y are each 1 or more; x / y is equal to or greater than 0.63 and equal to or less than 4.2, The weight average molecular weight is 5,000 or more and 300,000 or less.
Citation Information
Patent Citations
Thick plate for DC magnetization and preparation thereof
JP1985096749A